Pengaruh Pemanfaatan Teknologi Dalam Pelayanan Publik Perangkat Desa Kalukuang Kecamatan Galesong Kabupaten Takalar - Adhimsyah, Raizal; Said, Akbar (LPPM STIA Lancang Kuning Dumai, 2024)
This research aims to re-examine the contribution of the use of technology in public service services in Kalukuang village, Galesong sub-district, Takalar district. The research used is quantitative research with an associative approach. Data collection used primary data obtained from village officials by distributing questionnaires and sampling using saturated samples with a sample size of 32 respondents. Data was collected using research instruments in the form of questions which were measured using a Likert scale. Data analysis was carried out using multiple linear regression analysis. The research results show that the use of technology has a positive and significant influence in improving public services for village officials.